Autism friendly cities : how to develop an inclusive community - Percival, Jennifer Pollack (New York : Productivity Press, 2022)
Access. Inclusion. Diversity. All people deserve to be embraced by their community. Autism Friendly Cities: How to Create an Inclusive Community is the first book designed to guide city leadership and staff through the processes of training and evaluation, development, and implementation of an Autism Friendly initiative that will help you open your doors to everyone. People with autism should be able to participate in all that is offered and facilitated by their city, including services, activities, events, and points of connection. Being an Autism Friendly City is not only socially responsible, it will improve engagement, outreach, economic development, and resident satisfaction.
Part 1: THE WHY: WHY ARE WE HERE? WHY DOES THIS MATTER? Chapter 1: The Good, The Bad, and The PR Nightmares The Good The Bad PR Nightmares *Reflection: The Good and The Bad A Dialogue: DEIA Consider Your City *Brainstorm: Evaluate Your City Chapter 2: Recruiting Others Who Is at the Forefront of This Movement? What is the Time Commitment? How Do We Pay for This? Economic Development Chapter 3: Listen to Your Community Survey Your Residents *Resident Survey/Needs Assessment What You Might Hear Tend Your Garden Part 2: THE WHO: PEOPLE WITH AUTISM, LEADERS, AND COMMUNITY PARTNERS Chapter 4: Let's Talk a Bit about Autism *Quiz (Pre/Post Test): A Brief Quiz on Autism Basic Diagnostic Information Prevalence Characteristics Difference Versus Deficit Neurodiversity Hard Conversations *Pre/Post-Test Quiz Answers Chapter 5: Training What Training Does My Team Need/ *Worksheet: Questions for Potential Trainers How to Continue the Conversation Chapter 6: Putting Together Your Inclusion Team: Community Partners Are Key Develop Your Inclusion Team *Worksheet: Create Your Inclusion Team Potential Community-based Team Members Location and Timeframe for Meetings Inclusion Team Meeting Agenda Sample Inclusion Team Meeting Agenda Team Collaborations and Projects Regional or Statewide Inclusion Teams Part 3: THE WHAT: CREATING CHANGE Chapter 7: Getting Started *Worksheet: What Does Inclusion Look Like for Your City? Chapter 8: Environmental Modifications Sight Hearing Touch Smell Taste Temperature Spatial High and Low Sensory Spaces *Worksheet: Design your Space Chapter 9: Communication Techniques First Point of Contact Universal Design Website Using Direct Communication One-on-One Communication *Resident Meeting Agenda Template Chapter 10: Visual Supports *Sample Visual Support Template *Sample Visual Support Incorporating Directions *Sample Visual Support Where Graphics Are Incorporated into Existing Document Chapter 11: Social Sciences What is a Social Story? What Must a Social Story Contain? How Can I Create a Social Story? *Sample Social Story Chapter 12: Designing Large-Scale Events Chapter 13: An Example: Libraries Low Sensory Library Spaces Sensory Friendly Browsing Autism Friendly Programming *Sample Autism Friendly Program Registration Form Sensory Friendly Movie Night Sensory Friendly Story Time Chapter 14: Summer Camp Inclusion/IRPs *IRP (Individualized Recreational Program) Sample Chapter 15: Employment and HR Tips Chapter 16: Conclusion: Share with Others Success Stories Conference/Expo Overall checklist Declaring You Are an Autism Friendly City Tell the World
OCLC-licensed vendor bibliographic record.
Keywords: Autism -- Social aspects; Social integration; BUSINESS & ECONOMICS / Government & Business; BUSINESS & ECONOMICS / Urban & Regional; SOCIAL SCIENCE / Handicapped